Ripensare la scuola dopo la pandemia - Amalfitano, Elisabetta; Barbagli, Alessia (Il sogno della farfalla, 2021)
In this paper the authors discuss how schools as a daily fundamental social environment, already affected by critical issues before the outbreak of Sars Cov 2, have been among the most impacted sectors during the pandemic. Distant learning carried out during the two lockdowns has highlighted disparities among students and has not always guaranteed the primary objective of equality, as stated in the article 3 of the Italian Constitution. The lack of technological skills and educational training among teachers, familiar and intra-regional disparities and finally, the online teaching modality itself, have reduced teaching to a mere transmission of information. The social dimension of learning and teaching has been impoverished, therefore denaturing the conception of school itself. The authors highlight how crucial is to start from the most critical aspects emerged and exacerbated in the last two years to rethink the Italian teaching-educational model in the light of a new anthropology.